Epidemiology Symptomatology And Control Of Leaf Scald Disease Of Rice - Jayaram KP (Department of Plant Pathology, College of Agriculture, 1989)
Rhynchosporium oryzae, the causal organism of leaf scald disease of rice, was isolated and studies were conducted on the symptomatology, morphology, cultural characters, host range, toxin production and control of the pathogen. On rice plants, lesions were found to develop from the tips of leaves and the characteristic symptom was the formation of concentric zonations with brown margins, on the lesions. Symptoms were also found to occur on the leaf sheaths. Studies on the morphology of the fungus revealed that mycelium was hyaline, septate, and 2 to 3 µm broad. Conidia were two-celled and fusiform, measuring 10 to 14 µm x 3 to 4 µm. The organism was grown on different solid and liquid media. The studies revealed that among solid media, potato dextrose agar (PDA) was most suited for growth and sporulation of the fungus. Among liquid media, maximum dry weight of mycelium was obtained in potato dextrose broth. Sporulation was found to be maximum in potato dextrose broth and peptone glucose medium. Studies on the effect of varying levels of Nitrogen (peptone) and carbon (glucose) on growth and sporulation of the organism revealed that maximum dry weight of mycelium was obtained at 1 per cent Glucose and 1 per cent Peptone. Sporulation was maximum at lower levels of Carbon – 0.5 and 0.25 per cent. Starch was found to be the most suited source of Carbon for promoting the growth of the organism, and Peptone, the most suited source of Nitrogen. Studies showed the temperature of 300C and PH of 6.5 were optimum for the growth of the organism. Sporulation was found to be maximum at 25-300C. Of the twelve rice varieties tested, Mo-6 and Cul-25331 were found to be most resistant, and Mo-7, cul-204, Cul-153-1 and Jaya proved to be most susceptible. Studies conducted on the toxin produced by R. oryzae in culture revealed that the toxin by itself was able to cause typical leaf scald symptoms when sprayed on healthy rice plants. The toxin also inhibited germination of brinjal and paddy seeds and caused an appreciable decrease in the length of radical and plumule of paddy seeds. Host range studies showed that Cynodon dactylon, Cyperus rotundus, Hemidesmus indicus and Panicum repens developed scald symptoms when inoculated with the fungus. Laboratory studies revealed that cent per cent inhibition of spore germination was obtained by using Carbendazim at 500 ppm, 1000 ppm and 1500 ppm, Tridemorph at 1500 ppm, Captafol at 2000 ppm, 2500 ppm and 3000 ppm and Mancozeb at 2000 ppm, 2500 ppm and 3000 ppm. Studies following poisoned food techneques showed that Carbendazim at 500 ppm, 1000 ppm and 1500 ppm Tridemorph at 1000 ppm and 1500 ppm, Mancozeb at 2000 ppm, 2500 ppm and 3000 ppm, caused cent per cent inhibition of radial growth of R. oryzae. Pot culture trial with five fungicide revealed that after 2 sprays, Carbendazim, Mancozeb and Captafol were superior to Tridemorph and Carboxin in keeping the disease under check. Field trial showed that all the four different fungicides were effective in reducing disease intensity. The plots sprayed with Carbendazim recorded the least disease intensity. Studies on antagonistic activity of phylloplane mycoflora of rice on R. oryzae showed that Chaetomium globosum and Penicillium oxalicum might have some antagonistic effect on R. oryzae.